Charismatic Resilience and Community Empowerment: Religious Authority, Ecological Practices, and Climate Adaptation in an Indonesian Pesantren - Amrulloh, Zaenudin; Ummah, Athik Hidayatul; Muliadi, Erlan; Padli, Erwin (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
While Green Islam has attracted scholarly attention as a normative discourse, empirical research on how pesantren operationalize ecological resilience remains limited. This study examines the resilience processes of Pesantren Sirajul Huda and its surrounding community in Central Lombok in responding to climate-related challenges and post-pandemic socio-economic pressures. Employing an interpretive case study design and Kumpfer’s (1999) resilience framework, the study explores how resilience is constructed through the interaction of religious authority, social capital, ecological practices, and community participation. The findings reveal that resilience within the pesantren is not merely a technical response to environmental challenges but a religiously grounded social process. Religious authority, trust-based social relations embedded in the notion of barakah, and institutional participation function as key protective factors that mobilize collective action. Through ecological education, organic farming, and vocational programs, environmental stewardship is translated into practical adaptation strategies that support supplementary subsistence, livelihood diversification, and community well-being.The study extends Kumpfer’s framework by proposing the concept of charismatic resilience, defined as community resilience facilitated by the interaction of religious authority, trust-based social relationships, and institutional mechanisms of collective mobilization. These findings demonstrate how Islamic educational institutions can integrate religious values with climate adaptation practices to strengthen social well-being and adaptive capacity.